Ionizing radiation alters functional neurotransmission in Drosophila larvae - Zhang, Yi; Zhang, Yihao; Shen, Cong; Hao, Shun; Duan, Wenlan; Liu, Li; Wei, Hongying (Frontiers in Cellular Neuroscience, 2023)
Patients undergoing cranial ionizing radiation therapy for brain malignancies are at increased risk of long-term neurocognitive decline, which is poorly understood and currently untreatable. Although the molecular pathogenesis has been intensively researched in many organisms, whether and how ionizing radiation alters functional neurotransmission remains unknown. This is the first study addressing physiological changes in neurotransmission after ionizing radiation exposure. To elucidate the cellular mechanisms of radiation damage, using calcium imaging, we analyzed the effects of ionizing radiation on the neurotransmitter-evoked responses of prothoracicotropic hormone (PTTH)-releasing neurons in Drosophila larvae, which play essential roles in normal larval development. The neurotransmitters dopamine and tyramine decreased intracellular calcium levels of PTTH neurons in a dose-dependent manner. In gamma irradiated third-instar larvae, a dose of 25 Gy increased the sensitivity of PTTH neurons to dopamine and tyramine, and delayed development, possibly in response to abnormal functional neurotransmission. This irradiation level did not affect the viability and arborization of PTTH neurons and successful survival to adulthood. Exposure to a 40-Gy dose of gamma irradiation decreased the neurotransmitter sensitivity, physiological viability and axo-dendritic length of PTTH neurons. These serious damages led to substantial developmental delays and a precipitous reduction in the percentage of larvae that survived to adulthood. Our results demonstrate that gamma irradiation alters neurotransmitter-evoked responses, indicating synapses are vulnerable targets of ionizing radiation. The current study provides new insights into ionizing radiation-induced disruption of physiological neurotransmitter signaling, which should be considered in preventive therapeutic interventions to reduce risks of neurological deficits after photon therapy.